Pengaruh Brand Image, Kualitas Produk, dan Fanatisme terhadap Keputusan Pembelian Marchandise Persela Store - Moh. Roy Arba’in; Ika Purwanti (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to examine the impact of Brand Image, Product Quality, and Fanaticism on purchase decisions for merchandise at Persela Store Lamongan. The research employs a quantitative approach to explore the causal relationships between these variables by testing the proposed hypotheses. The subjects of this study were customers who had previously made purchases at Persela Store Lamongan. The sampling method used was non-probability sampling with a purposive sampling approach, involving 100 respondents who met the research criteria. Data were gathered using a questionnaire distributed to the selected participants. The data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to determine the strength of the relationships between the variables. The study's findings reveal that Brand Image does not significantly influence purchasing decisions, whereas Product Quality and Fanaticism have a significant positive impact on consumers' purchasing behavior. Specifically, although Persela's brand strength, as a football club, is well-known, it does not appear to be a significant enough factor in encouraging consumers to make purchases. On the other hand, Product Quality and Fanaticism were identified as the main factors that drive purchasing decisions at Persela Store Lamongan. High-quality products and a strong emotional attachment to the club are essential factors that influence consumers to buy the merchandise. These results highlight the importance of product quality and consumer loyalty over brand image in influencing purchasing behavior, suggesting that Persela Store should focus more on enhancing product quality and fostering fan engagement to boost sales. This study contributes valuable insights for businesses aiming to improve customer purchasing decisions, especially in the sports merchandise industry, and offers recommendations on how to leverage product quality and fan enthusiasm to increase sales.